Management of temples with historical sites as eco-tourism destinations - VIJITSAK, PHRAKHRUSANGKHAKITVIRIYA (Wishing Journal Review, 2024)
This study aims to gain an understanding of temple management, with a specific organizational management model and conservation management model in which the abbot is the driving force in managing temples that have historical sites as sources. Ecotourism It is a source of learning about community culture. Therefore, the management of temples with historical sites requires participation and conservation of the unique culture and identity of that place. It is very important to understand the local context. and the cooperation of the local owner with the people and local organizations, with the abbot leading and creating a unified understanding in management for prosperity.